Uma visão bioecológica sobre atendimento infantil e práticas educativas no contexto de um serviço escola de psicologia - Machado, Juliana da Cas (2022)
The sociocutural changes that families, understanding of childhood and child development have suffered over the last two centuries are remarkable. However, until now family is identified as a microsystem of extreme relevance regarding children’s health development, due to it being the most frequent space for establishing the first, close and significant sort of relationships, presenting models for other children’s affairs and interactions with the biopsychosocial formation throughout life of everyone involved. It is noteworthy that child mental health has increasingly received more attention from public health and social assistance policies, since the homologation and search for effectiveness of the Statute of the Child and the Adolescent - ECA, Brazil 1990. Parallel to this, it can be noticed that adults who are legally responsible for children - parents and/or legal guardians - that take part in the child’s socialization processes have been searching for specialized places of psychological care for their children, in order to receive help and guidance for the daily demands and the specific care with their mental health. Among the available places are the School Services in Psychology of the Higher Education Institutes, that offer courses in Psychology, including different modalities of psychological care, such as those aimed at children. The present research was developed as an exploratory-descriptive study, collecting data and investigating it through instruments that value a quantitative-qualitative approach which was aimed to describe and analyze the information contained in 67 registration forms and 54 screening interviews filled out by adults responsible for children who sought psychological care in a School Service in psychology of a Federal University in the Midwest in 2019 for their children. The research also shows the results of identification and evaluation of educational practices in the daily lives of 12 of those children, through the application and analysis of 15 Parenting Styles Inventories - IEP (nine children had the IEP answered by one parent while three were answered by both parents) and the field records diary of the researcher on the application of these IEPs. This study was based on the Bioecological Model of Human Development - MBDH, the data analysis was executed by means of the following processes: application and screening forms were read and the reports were sectioned into categories according to the Quantitative Interpretative Model (Biasoli-Alves, 1998), the IEPs were analyzed in rapport to the manual (Gomide, 2011) and the field diary was used within a qualitative-descriptive proposal (Alves, 2002). The study also presents that most parents make use of negative educational practices, mainly through physical aggression and punishments. Although they recognise that those actions are not adequate, the parents are not able to handle their children in a different way. In most of the families that responded to the IEPs, mothers are both responsible for taking care of the children and of the house, including financial issues, that shows how women got centered with physical and emotional burdens. Throughout the research it could be observed how much family's support is restricted, which points out a greater vulnerability of the family as a microsystem. Likewise, it was evident that children have fewer opportunities for social and affective interactions, other than those experienced with family and in school. It was noticed that the protective factors, both individual and environmental, rarely appear in families, demonstrating the need for interventions focused on constructing and maintaining protective factors. It was verified that the responsible adults seek the Psychology Services in an attempt to find help for the demands and complaints presented in a variety themes about childhood and development, evidencing the significant role of the Services regarding guidance and care with these families and children. It is essential to emphasize that this research was developed before the COVID-19 pandemic and much of the presented and discussed topics have new and important structures to be known and reflected as of March 2020 and all the demands generated by the isolation, social distancing, suspension of face-to-face activities for the general population, deaths due to the pandemic and other aspects that deserve attention to all psychologists practice daily, especially within their formation in a School Service of Psychology.